Pengaruh Variasi Jenis Koil dan Mapping Derajat Pengapian Menggunakan Programmable CDI Terhadap Daya Pada Motor Bensin 110 CC - Aprilian Rizki Triatmoko; Purwoko Purwoko (Pusat Riset dan Inovasi Nasional, 2024)
The rapid development of transportation technology, especially in motorbikes, has increased interest in modifications to enhance performance. Improving motorbike performance involves modifying the ignition system by upgrading the CDI and replacing standard coils with aftermarket ones. This aims to enhance engine performance since standard CDIs have relatively low output power and standard coils have limited output capacity, necessitating compatible CDI and coil upgrades.This research focuses on improving the performance of a 110cc 4-stroke engine using experimental quantitative methods and data analysis. The independent variable is aftermarket coil variations with higher voltage (up to 90 kV) and ignition mapping with a Programmable CDI. The dependent variable is power output. Data processing involves two-way ANOVA analysis of test result graphs processed in Microsoft Excel, averaging results from three tests per variation.Results show that setting the ignition at the 13th degree and using a BRT coil provided the highest power output, reaching 8.33 horsepower at 8000 RPM. This is because effective ignition timing and larger sparks are crucial for regulating fuel combustion in the chamber, leading to earlier and more powerful explosions..